2020
DOI: 10.1177/0033688220926715
|View full text |Cite
|
Sign up to set email alerts
|

Perennial Language Learners or Competent Language Users: An Investigation of International Students’ Attitudes towards Their Own and Native English Accents

Abstract: English is widely used as a global language. The traditional monolithic model of English has been challenged as the development of World Englishes (WE) and English as a lingua franca (ELF) paradigms challenge the ownership of English. With this newly emerging status quo, English language teaching (ELT) should also recognize the diversity and dynamism of English. This article discusses students’ attitudes towards their own and native English accents, and describes the influence of English accents in ELT. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…In Thailand, it is observed that three Global Englishes research areas were conducted: 1) language attitudes (e.g., Boonsuk & Fang, 2022;Thienthong & Uthaikorn, 2023), 2) Global Englishes classroom implementation (e.g., Boonsuk et al, 2021;Jindapitak et al, 2022;Rajprasit, 2022), and 3) Global Englishes teacher professional development (e.g., Prabjandee, 2020;Prabjandee & Fang, 2022). This study contributes to the first line of inquiry (language attitudes) since it offers valuable resources for ELT practitioners when considering implementing Global Englishes in the classrooms.…”
Section: Global Englishes and Language Attitude Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In Thailand, it is observed that three Global Englishes research areas were conducted: 1) language attitudes (e.g., Boonsuk & Fang, 2022;Thienthong & Uthaikorn, 2023), 2) Global Englishes classroom implementation (e.g., Boonsuk et al, 2021;Jindapitak et al, 2022;Rajprasit, 2022), and 3) Global Englishes teacher professional development (e.g., Prabjandee, 2020;Prabjandee & Fang, 2022). This study contributes to the first line of inquiry (language attitudes) since it offers valuable resources for ELT practitioners when considering implementing Global Englishes in the classrooms.…”
Section: Global Englishes and Language Attitude Researchmentioning
confidence: 99%
“…Considering that English is dynamic and changing, as described in the Global Englishes paradigm, previous studies have investigated teachers' attitudes toward Global Englishes (e.g., Ahn, 2015;Huttayavilaiphan, 2019;Monfared & Khatib, 2018) and learners' attitudes toward Global Englishes (e.g., Boonsuk & Fang, 2022;Chan, 2018). These studies pointed out that teachers and learners generally perceived English varieties as non-standard, reflecting the traditional views of English use.…”
Section: Global Englishes and Language Attitude Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitation of the research was the use of manual analysis and weak samples. However, Yusop and Fan [15] utilized a qualitative approach with semi structured interviews as the method of data collection. The data analysis was carried out with VIVO software, which addresses the limitations of the earlier research.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, British English and American English remain the only approved ELT models in Thai and many other ELT markets (Boonsuk et al, 2021;Jindapitak & Boonsuk, 2018;Galloway & Rose, 2015Rose & Galloway, 2019). The problem is that this traditional EFL teaching approach relies heavily on NES norms which cultivates Thai learners with a set of attitudes towards English language, i.e., NES's standard English varieties and Native English Speaking Teachers (NESTs) are highly valued, efficient, widely accepted, correct, ideal, and professional; whereas NNES's non-standard English and non-native English speaking teachers (NNESTs) are less appreciated, inefficient, socially flawed, incorrect, impractical, and unprofessional (Boonsuk & Fang, 2020;Jindapitak & Teo, 2012). The approval of NEST and disapproval of NNEST in English language education is not a new phenomenon in Thailand.…”
Section: Literature Review English Language Teaching Ideology In Thailandmentioning
confidence: 99%